The underground railroad - Bial, Raymond (New York : Houghton Mifflin, 1995)
By ones, twos, and threes, in the years before the Civil War thousands of enslaved people slipped through the night on their way to freedom, riding the Underground Railroad. Hidden and hunted, the escape of southern slaves to the North remains a compelling event in American history. Within the pages of this book are documented, in prose and elegantly articulate photographs, examples of "stations" on the Railroad, along with images of the routes, lives, and hardships of both the "passengers" and "conductors."
Includes bibliographical references (p. 46-47).
Keywords: Underground Railroad -- Juvenile literature; Fugitive slaves -- United States -- History -- 19th century -- Juvenile literature